ESTIMATES OF GENETIC VARIANCE COMPONENT OF AN EQUILIBRIUM POPULATION OF CORN - Hamirul Hadini; Nasrullah Nasrullah; Taryono Taryono; Panjisakti Basunanda (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
There are abundant maize populations in Hardy-Weinberg equilibrium, which can be used as source of gene to develop either a hybrid variety or an open pollinated variety. Genetic parameters of a population, such as additive genetic variance and variance due to dominance which can be estimated using North Carolina Design I, were used to decide a breeding method to be applied. The objectives of this research were to estimate the genetic variance component of important quantitative traits in an equilibrium corn population and to decide the best method to develop the population. The research was conducted at Agricultural Station of Agriculture Faculty, Gadjah Mada University, in 2012 which was carried out in two steps: to develop half-sib and full-sib families and to evaluate both families in randomized complete block design with three replications. The data was subjected to analysis of variance, and was followed by estimation of genetic variances. The additive variance of ear length and ear diameter of the corn population was greater than dominance variance. In contrary to kernel weight/ear, the dominance variance was greater than additive variance. So based on kernel weight/ear, the Hardy-Weinberg equilibrium corn population can be developed through inbreeding to form a hybrid variety.